Communicative English Training Using the (Role-Play) Method for Souvenir Traders at the Sasak Pottery Craft Center, Penujak Village - sumarni, baiq; Terasne, Terasne; Permana, Dira; Nafisah, Baiq Zuhrotun (Abdi Masyarakat, 2024)
This community service program aims to improve English communication skills for souvenir sellers of pottery crafts in the Sasak handicraft Center, Penujak Village, Central Lombok Regency. The program utilizes a role-play-based training method, consisting of three main sessions: Theoretical Learning, where participants learn vocabulary, phrases, and basic communication techniques for interacting with tourists; Practical Role-Playing, where participants practice roles as buyers or sellers using prepared scenarios and receive feedback from instructors; and Realistic Simulation, where participants engage in real-life interactions with foreign tourists. The program also includes initial observations, preparation, implementation, and evaluation. The program's partners are 30 souvenir sellers from Sasak Pottery. Evaluation is carried out through direct observation of the participants' use of English vocabulary and phrases. The results show that: 1) Participants have gained theoretical knowledge of basic communication concepts, and 2) participants are able to apply vocabulary and phrases in their communication skills with foreign tourists, especially in selling products. This training is expected to have a positive impact on the well-being of the community, particularly the craftsmen and souvenir sellers in Penujak Village.